Research on Acceptance and Testing Scheme of Intelligent Distributed Feeder Automation System. (August 2020) - Wang, Yifan; Huang, Yibiao; Wu, Linwei; Wu, Yiping; Wang, Yu
Abstract: The intelligent distributed FA uses the peer-to-peer communication network between distribution terminals to realize the information exchange between terminals, and uses the line fault state quantity differential and bus fault state quantity differential to realize the fault monitoring, fault isolation and non-fault area restoration of power supply. In the distribution automation system, the proportion of terminals with intelligent distributed FA function is increasing. How to test and accept such terminals has become a research hotspot. This paper introduces the basic test contents of testing intelligent distributed FA through simulation system, and expounds the ideas and methods of test and acceptance in detail. Some suggestions are given for the test and acceptance of intelligent distributed FA terminal, which can be used for reference to improve the test standard and batch test.